The Impact of Air Pollution and Haze on Hospital Admissions for Cardiovascular and Respiratory Diseases - Norfazillah Ab Manan,; Rozita Hod,; Mazrura Sahani,; Hanizah Mohd Yusoff,; Rosnah Ismail,; Wan Rozita Wan Mahiyuddin, (Universiti Kebangsaan Malaysia, 2016)
Air pollution has been widely known to have an influence on health of the general population.Air pollution can result from natural causes, human activities and transboundary air pollution. Weather and climate play crucial role in determining the pattern of air quality. In recent years, air pollution and recurrent episodes of haze has become a major concern in Malaysia. Surveillance data on concentrations of main air pollutants such as carbon dioxide, (CO2), Nitrogen Dioxide (NO2), Ozone (O3), sulphur dioxide (SO2) and particulate matter (PM10) were found to be higher during the haze days and this may have an impact on health of the community as reflected by an increase in hospital admissions particularly the respiratory and cardiovascular diseases.